EndophyticBbacteria origin of healthy rice plants produce antifungal volatile compound inhibited the growth of Pyricularia oryzae Cav., the causal agent of rice blast disease - Fitri Widiantini; Fuji Hartati (CROPSAVER, 2020)
Endophytic bacteria have been known as producers for bioactive compound in which widely used in the field of crop protection. Several isolates of endophytic bacteria have demonstrated their potential ability as biocontrol agents by inhibiting the development of major rice pathogens. However, their ability to produce bioactive compounds has not been explored. The study reported the ability of the endophytic bacteria isolates in producing antifungal volatile compounds to inhibit the growth of Pyricularia oryzae Cav., the causal agent of rice blast disease. The experiment was conducted by dual culture method using bipartite compartments in which the bacterial isolates and P. oryzae were grown separately and placed by facing to each other. The bacterial isolates were grown on ISP2 agar media, whereas P. oryzae was grown on PDA media. Nine isolates were tested for their ability in producing antifungal volatile compound. The potential of antifungal volatile compound was observed by the P. oryzae growth compared to control. Furthermore, its effect on the P. oryzae mycelia was observed under microscope. The result demonstrated that all of the tested isolates were able to produce volatile compound which were able to inhibit the growth of P. oryzae. In addition, the compounds were also causing mycelial alteration.